Phytochemical analysis and antioxidative properties of Centaurea albonitens - S. Hamedeyazdan; F. Niroumand; F. Fathiazad (Iranian Society of Pharmacognosy, 2017)
Background and objectives: Thegenus Centaurea from the Asteraceae family is one of the most widely distributed plant genera worldwide that has been extensively used in folk medicine for hundreds of years. The present study is the first investigation about the principal constituents of Centaurea albonitens Turrill which is native to Iran. Methods: Theaerial parts of C. albonitens were extracted via maceration. Phytochemical analysis of the methanol extract was carried out via different chromatography approaches like HPLC, SPE and preparative TLC. Structures of the purified compounds were revealed through spectral analysis from 1D and 2D NMR including DQF-COSY, HSQC and DEPT in comparison with the relative data in published reports. Subsequently, the antioxidant property of the extract was evaluated via scavenging the free DPPH radicals. In addition, the total phenolic and flavonoid contents of the extract were ascertained based on Folin-Ciocalteu and colorimetric aluminum chloride methods, correspondingly. Results: Analysis of the extract yielded in the isolation and identification of arctiin and apigenin-4'-O-rhamnoside. Moreover, the antioxidant assessment determined IC50 value of 389.9 µg/mL for the plant extract in DPPH assay. The total phenolics and flavonoids content of the plant extract were 2.87 g gallic acid equivalent and 0.28 g quercetin equivalent both in 100 g dried plant material. Conclusion: The findings of this study introduce C. albonitens as a suitable source for isolation of lignans (like arctiin).